THE ROLE OF FAMILY SUPPORT ON DIETARY ADHERENCE IN PEOPLE WITH DIABETES MELLITUS - Vido Deriansyah; Ardhiles Wahyu Kurniawan; Bayu Budi Laksono (HEARTY, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by high blood sugar levels due to impaired insulin secretion or function, and it is one of the leading causes of morbidity and mortality worldwide. One of the important components in managing DM is adherence to a regular and recommended diet. This study aimed to determine the relationship between family support and dietary adherence in people with Diabetes Mellitus. The study used a correlational analytical design with a cross-sectional approach, involving 50 individuals with DM as respondents. Data collection was carried out using questionnaires, and the data were analyzed using the chi-square test. The results showed a relationship between family support and dietary adherence in patients with Diabetes Mellitus with a p-value of 0.002 (α = 0.05). These findings indicate that family support plays an important role in improving dietary adherence in people with Diabetes Mellitus and emphasize the need for family involvement in diet management education and interventions to optimize disease control.